Effect Walking Exercise In Patient With Diabetic Peripheral Neuropathy : A Follow Study - Fitriyah, Oktaviani; Komalasari , Dwi Rosella (Gaster, 2024)
High blood sugar levels are a symptom of diabetes mellitus (DM), a metabolic condition brought on by insulin insufficiency as a result of pancreatic dysfunction and insulin resistance. Reduced perception of touch, warmth, pain, and proprioceptive input are symptoms of diabetic peripheral neuropathy (DPN), which impairs perception of ambulation and raises the risk of falls. A doctor diagnosed the patient, a 62-year-old woman, with type 2 diabetes ten years ago. The patient is free of cerebral ataxia, neurological, and cardiovascular conditions, and is able to walk without the need for assistance. It was noted that the patient had fallen once in the previous twelve months. The patient has good verbal comprehension skills. Between the patients who exercised walking and those who did not, there was a notable difference. The sixth exercise, when the score displays the maximum number, is where the average training score indicates improvement. The T6 score on the MNSI exam revealed a value of 1.5. Pain during rest, standing, walking, and during vigorous activity all showed a maximum decline in measurements at T6. Similar to previous measurements, T6 is where the maximum value is found. Walking is thought to help diabetes patients with peripheral neuropathy with their balance, strengthen their lower limb muscles, reduce discomfort, enhance cognitive function, enhance psychosocial elements, enhance quality of life, and enhance social interaction.